Implications of using fermentation plant extract formulations against pests and predator in rice plants. Issue 1 (1st December 2022) - Farida; Sjam, S; Rosmana, A; Sulaeha; Dewi, V S; Wardiman, M A; Husain, A
Abstract: Currently the use of plant extracts to reduce pest attacks is a concern. Mixed formulation of two plant extracts Calatropis gigantea and Crescentia cujete was applied in the filed rice to assess the effectiveness of these formulations in reducing insect pest populations and predatory (natural enemies). The results showed that the combination of C . gigantea and C. cujete in one formulation could reduce the population of the main pests of rice plants and did not affect the presence of natural enemies (predators). The field trials showed that mixing C . gigante and C . cujete in liquid formulation reduced pest population compared the farmer with treatment synthetic pesticide. Population decrease of scipophaga innotata with range 21-77 percent, Cnaphalocrosis medinalis 25-79 percent. The abundance of pests was very low when using the plant extract formulation, whilst the synthetic pesticide generally had a higher number of pests. Predator numbers were higher in plant extract formulation and low with synthetic insecticide by farmer application. Synthetic insecticides have a very large impact on predators while plant extract formulations have no impact because the predator population is still higher than application by synthetic. Plant extract formulation (mixed C . gigantean and C . cujete ) is more effective in reducing population pests than synthetic pesticides. The plant growth parameters were better in the treatment of plant extracts formulation than the application by farmer. This research indicated that using plant extracts formulation effective to control pests can be as effective compared as synthetic insecticides by using of farmer.